Applying the Theory of Motivated Information Management to the Context of Conflicting Online Health Information: Implications for Childhood Vaccination Communication with Parents. Issue 5 (19th October 2020) - Li, Jo-Yun; Wen, Jing; Kim, Joon; McKeever, Robert
ABSTRACT: This study investigates how parents manage conflicting online information, which may affect their information-seeking behavior and decision-making about childhood vaccination, by applying the Theory of Motivated Information Management in online communication contexts. Although an extensive body of literature has demonstrated the effectiveness of TMIM in predicting how individuals manage health uncertainty and information in the interpersonal communication contexts, the present study goes beyond and applies the theoretical framework in the online communication contexts. Our findings of a survey with 439 parents in the United States are in conjunction with previous applications of TMIM, which show that individuals adopt a similar process to deal with uncertainty resulting from conflicting information in the online environment. Although further research must be conducted to change perceptions, attitudes, and vaccine-related behaviors, this study may help communication practitioners, vaccination advocates, and related nonprofit organizations to eliminate misconceptions about immunization among parents.